Faktor-Faktor yang Mempengaruhi Minat Siswa Kelas XI Tahun Pelajaran 2024/2025 SMA Negeri 1 Rejotangan dalam Melanjutkan Pendidikan ke Perguruan Tinggi - Saputri, Natasya Triana; Nurmaning, Bina Andri (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to determine the factors that influence the interest of class XI students in the 2024/2025 academic year of SMAN 1 Rejotangan in continuing their education to college. The method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 80 students. The results of the analysis show that there is a positive influence of internal factors on the interest in continuing education to college with a calculated t value of 7.134 which is greater than the t table (2.999) and a significance value of 0.000 which is smaller than 0.05. In addition, external factors also have a positive effect on interest in continuing education to college, with a t value of 3.558 which is also greater than the t table (2.999) and a significance value of 0.000. Simultaneously, these two variables make a significant contribution to the interest in continuing education to college, with a calculated F value of 144.886 which is much greater than the F table (2.56) and a significance value of 0.000. From the results of this study, it can be concluded that internal factors and external factors have an important role in shaping students' interest in continuing their education to college.